(untitled) (Applied Biological Research, 2017)
The present study was aimed to assess the antioxidant potential of methanolic extract of pomegranate (Punica granatum) by in vitro assays and in vivo model. Under in vitro conditions the antioxidant activity of methanolic extract of pomegranate fruit was 198.3, 192.2, 181.1 and 143.2 mg 100 g-1 by DPPH, nitric oxide, superoxide radical scavenging assays and ferric reducing antioxidant power assay, respectively. Under in vivo conditions, the levels of antioxidant enzymes superoxide dismutase, catalase, glutathione peroxidase were increased and lipid peroxidation level decreased after supplementation of fresh fruits. The free radical scavenging and antioxidant activities may be ascribed to the presence of total polyphenols (148.6 mg 100 g-1), total flavonoids (209.8 mg 100 g-1) and ascorbic acid content (24.2 mg 100 g-1) in pomegranate fruits. The results indicate that pomegranate fruit is a potential source of natural antioxidant.